2014
DOI: 10.1026/0049-8637/a000114
|View full text |Cite
|
Sign up to set email alerts
|

Professionelle Unterrichtswahrnehmung von Lehramtsstudierenden

Abstract: Zusammenfassung. Im Rahmen einer deutschlandweiten Scaling-up Studie wurde eine Prüfung des Kompetenzmodells der Professionellen Unterrichtswahrnehmung mit dem Tool Observer an einer Stichprobe von N = 1029 Lehramtsstudierenden vorgenommen. Als Teil der Validierung des Instruments wurde untersucht, inwieweit das Instrument bei Studierenden unterschiedlicher Lehramtsstudiengänge vergleichbar eingesetzt werden kann. Analog zu den Befunden der Skalierungsstudie (N = 152) kann Professionelle Unterrichtswahrnehmung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
4
0
5
Order By: Relevance
“…Analyses of the psychometric properties of the instrument based on item response theory have confirmed that the Observer tool provides a valid and reliable assessment of professional vision (Jahn et al 2014;Seidel and Stürmer 2014). In two scaling…”
Section: Methodsmentioning
confidence: 90%
“…Analyses of the psychometric properties of the instrument based on item response theory have confirmed that the Observer tool provides a valid and reliable assessment of professional vision (Jahn et al 2014;Seidel and Stürmer 2014). In two scaling…”
Section: Methodsmentioning
confidence: 90%
“…Student responses were compared to the expert norm and recoded into 0 = miss expert rating and 1 = hit expert rating . Analyses of the psychometric properties of the instrument based on Item Response Theory (IRT) have confirmed that the Observer provides a valid and reliable assessment of professional vision (Jahn, Stürmer, Seidel, & Prenzel, 2014;Seidel et al, 2010b). In two scaling studies with more than 1,000 preservice teachers from different universities who were educated for various school tracks (i.e., primary, secondary), three models that might describe the structure of professional vision (one-, two-, and three-dimensional) were applied and scaling results were compared.…”
Section: Assessing Professional Vision: the Observer Toolmentioning
confidence: 99%
“…Zur Untersuchung der professionellen Unterrichtswahrnehmung von (angehenden) Lehrkräften liegen bereits validierte fachunabhängige (Jahn et al 2014 Um das Konstrukt situative Beobachtung und Wahrnehmung änderungssensitiv und zeitökonomisch zu messen, bietet es sich an, das Instrument auf einen mathematischen Inhaltsbereich zu fokussieren -auch wenn frühe mathematische Bildung verschiedene mathematische Inhaltsbereiche adressieren sollte (Benz et al 2015). Da die zentrale Rolle arithmetischer Basisfertigkeiten für die mathematische Entwicklung empirisch gut belegt ist (bspw.…”
Section: Potenzielle Einflussfaktoren Auf Situative Beobachtung Und Wunclassified